Stochastic mathematical models (Latakia University Journal -Basic Sciences Series, 2019)
The purpose of this research is to study and create a stochastic mathematical model based on a renewable energy source (wind).The question of finding optimal values for the variables of the mathematical model subject to stochastic conditions is one of the random mathematical problems, which require special stochastic methods to solve in the general case.